Topological delocalization of two-dimensional massless Dirac fermions - Nomura, Kentaro; Koshino, Mikito; Ryu, Shinsei (arXiv.org, 2007)
The beta function of a two-dimensional massless Dirac Hamiltonian subject to a random scalar potential, which e.g., underlies the theoretical description of graphene, is computed numerically. Although it belongs to, from a symmetry standpoint, the two-dimensional symplectic class, the beta function monotonically increases with decreasing \(g\). We also provide an argument based on the spectral flows under twisting boundary conditions, which shows that none of states of the massless Dirac Hamiltonian can be localized.